Plasminogen Activator Inhibitor-1, Diabetes, and Vascular Disease - Jung, Richard (Université d'Ottawa / University of Ottawa, 2022)
Patients with established coronary artery disease (CAD) remain at elevated risk of major adverse cardiac events (MACE). Specifically, stented coronary artery remains the highest-risk coronary lesion with annualized adverse event rates as high as 8-12% in the following year largely due to in-stent restenosis (ISR) and stent thrombosis. Plasminogen activator inhibitor-1 (PAI-1), an anti-fibrinolytic protein, has previously been associated with CAD with known mechanism of action to regulate the pathophysiological changes associated with in-stent restenosis and stent thrombosis. Moreover, extracellular vesicles (EVs) originating from circulating blood and vascular cells are increasingly being utilized as biomarkers and mediators of vascular disease. We first demonstrate the analytical and biochemical performance of plasma PAI-1 in patients with established CAD. Specifically, PAI-1 performs similarly to established biomarkers including C-reactive protein and NT-proBNP with an analytical (CVa = 4.1%), intra-individual (CVi = 44.0%), and inter-individual (CVg = 118.6%) coefficients of variation. Following this, we demonstrate that plasma PAI-1 is not associated with MACE in one-year follow-up, but reduced levels of PAI-1 remain associated with unplanned revascularization. Subsequently, we sought to evaluate the relationship between PAI-1 and EVs in humans with platelets being a common source of origin. In the largest study of EV to-date in CAD (n=489), we demonstrate the strong predictive ability of PAI-1 platelet-derived EVs (PAI-1+ PEV) with MACE following revascularization. Patients with high circulating levels of PAI-1+ PEV had higher rates of MACE (262.3 vs. 103.0 events per 1,000 person-years; hazard ratio (HR) 2.19; 95% CI, 1.07-4.52; and HR 2.67; 95% CI, 1.22-5.84, discovery and validation cohorts, respectively). Furthermore, we reveal that high PAI-1+ PEV fractions did not enhance thrombogenicity but promoted a pro-inflammatory vascular smooth muscle cell (VSMC) state by enhancing proliferation and migration, through up-regulation of pro-inflammatory genes such as KLF4. Inhibition of the PAI-1-LRP-1 interaction by TM5275 dampened the pro-inflammatory VSMC response, whereas inhibition of the PAI-1-vitronectin interaction by tiplaxtinin had no such effect. Our data reveals the potential of PAI-1+ PEV as a biomarker in the post-revascularization population and postulates the mechanism in an in vitro model of VSMCs. Accordingly, our data demonstrates the potential of PAI-1 PEV as a strong biomarker following revascularization and PAI-1 inhibition by TM5275 is a promising strategy to reduce the pro-inflammatory VSMC state associated with ISR.
Keywords: Coronary artery disease